The Effect of Using Thoracal Lumbar Sacral Orthosis (TLSO) on Alignment Kyphosis in the Elderly - Ningsih, Cica; Fathi, Muhammad (Poltekkes Kemenkes Jakarta I, 2023)
Introduction: The alterations that occur in the vertebrae are Kyphosis, Lordosis, and Scoliosis. Kyphosis affects the majority of the elderly. Kyphosis is a type of deformity wherein the human spine becomes bent. The most frequent alterations in the vertebrae are atilted head forward (cervical kyphosis), an increase in the thoracic kyphosis curve, a flattened lumbar curve (lumbar kyphosis), and a reduction in the width of the intervertebral discus, resulting in a lower height. The focus of this research was to study the effects of TLSO on vertebral alignment postures in older people with kyphosis. Method: This research is a quasi-experimental research with one group pre and posttest design techniques. This research was conducted from March to October 2021 at the PosyanduLansia Sawahan, Ngemplak, Boyolali. Elderly who meet the requirements for this research subject include up to 30 elderly people. Each study subject will receive the TLSO intervention and then assess their spinal alignment before and after treatment.Paired Samples T-test was used to analyze the data in this study. Result: The application of TLSO had a statistically significant effect on alignment before and after the intervention (t = 35.98, mean difference = 8.34, and p value = 0.000). Conclusion: The use of TLSO has an impact on reducing spinal curvature so it is good for maintaining body posture according to normal alignment.